PENGARUH KOMPENSASI TERHADAP KESEJAHTERAAN PEGAWAI NEGERI SIPIL: STUDI KUANTITATIF DI KANTOR CAMAT TILAMUTA - Syamsinah, Syamsinah; Lakoro, Fibriyanti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This research is motivated by observed issues such as absenteeism, tardiness, and low work engagement among employees. The purpose of this study is to examine the influence of compensation on the well-being of civil servants: A Quantitative Study at the Tilamuta District Office. The research method used is a quantitative approach with descriptive and verification techniques. The sample consisted of 34 civil servants who responded to a Likert scale questionnaire. Data analysis was conducted using simple linear regression. The results indicate that compensation has a positive and significant effect on employee well-being (R² = 71.3%, t = 9.300, p < 0.001). The regression equation Y = 3.251 + 0.609X suggests that an increase in compensation will enhance well-being. The findings are consistent with Herzberg’s two-factor theory, which emphasizes the role of compensation in improving job satisfaction and well-being.